Pemberdayaan Usaha Kecil Menengah Sepatu Melalui PenerapanTeknologi Emboss dan Perbaikan Manajemen - Ali Hasbi Ramadani; Yunus Yunus; Fandi Fatoni; Saiful Anwar (Jurnal Pemberdayaan Masyarakat, 2023)
The community service program carried out in Sidoarjo Regency aims to help solve priority problems experienced by shoe MSME partners. There are two priority problems that must be resolved to empower partner MSMEs to improve the quality and quantity of their production, namely: (1) low quality and quantity of leather shoe brand labeling production, and (2) poor financial management. Methods to overcome the problem of low quality and quantity of brand labeling production are carried out through the application of semi-automatic leather embossing machines with electric energy and to overcome poor financial management through training and mentoring of financial management with a participatory approach. The results of this community service program are: (1) Electric energy semi-automatic leather embossing press machine, 2) a simple cash book. The conclusion of the results of the implementation of PKM activities that have been carried out with partners is that by increasing the quality and quantity of partner shoe brand labeling production with a magnitude of 30 times faster or (3000%) increase besides that the financial management of partner SMEs has been carried out properly through recording business financial flows using simple ledger.